(untitled) (Research, Society and Development, 2022)
Objective: To address the aspects surrounding the diagnosis of adenomyosis, especially relating the histological findings of biopsies obtained by surgical hysteroscopy with clinical data suggestive of this pathology. Methodology: This is a retrospective observational and cross-sectional study, carried out from the analysis of questionnaires and test results from patients submitted to hysteroscopic biopsy, in a private hospital in the city of Divinópolis-MG. Data analysis was performed, especially between clinical symptoms and confirmation or not of adenomyosis in the anatomopathological samples. Results: It was possible to observe that the most prevalent symptomatology was menorrhagia (76.1%) and menstrual cramps (69.2%), in addition to the fact that the best results of the association of positive hysteroscopic biopsy for adenomyosis with the symptomatology were obtained from the comparison with more than 3 symptoms presented by the patients, with better sensitivity (60.7%), specificity (57.5%) and accuracy (58.8%) and, in the comparison with 3 symptoms, there was the highest negative predictive value (85, 7%). Conclusion: The analysis of biopsy results by surgical hysteroscopy, together with the management of associated symptoms, did not present sufficiently high results for its consolidation as a diagnostic test of adenomyosis in this study. Even so, the scarcity of data in the current literature on this comparison indicates the need to investigate the existence of other possible directions in the still imprecise diagnosis of this pathology, when approached by less invasive methods than hysterectomy.